Highly reliable memory-based physical unclonable function using spin-transfer torque MRAM - Kong, Zhi Hui (2015)
In recent years, Physical Unclonable Function (PUF) based on the inimitable and unpredictable disorder of physical devices has emerged to address security issues related to cryptographic key generation. In this paper, a novel memory-based PUF based on Spin-Transfer Torque (STT) Magnetic RAM, named as STT-PUF, is proposed as a key generation primitive for embedded computing systems. By comparing the resistances of STT-MRAM memory cells which are initialized to the same state, response bits can be generated by exploiting the inherent random mismatches between them. To enhance the robustness of response bits regeneration, an Automatic Write-Back (AWB) technique is proposed without compromising the resilience of STT-PUF against possible attacks. Simulations show that the proposed STT-PUF is able to produce raw response bits with uniqueness of 50.1% and entropy of 0.985 bit per cell. The worst-case Bit-Error Rate (BER) under varying operating conditions is 6.6 × 10-6.